Cultural Dynamics and Marital Relationship Quality in Mexican-origin Families - Cruz, Rick A. (J Fam Psychol, 2014)
Prior research suggests that acculturation may influence relationship outcomes among Mexican-origin married couples, including marital adjustment and distress. Despite much theory and research on parent-child cultural differences and disruptions in the parent-child relationship, no previous research has investigated possible associations between husband-wife cultural differences and marital relationship quality. With a sample of Mexican-origin married couples (N = 398), the current study investigated the relations between husband-wife differences in acculturation (American orientation) and enculturation (Mexican orientation) with husband and wife reports of positive marital qualities (warmth and relationship satisfaction). To clarify and extend previous research, the current study also investigated within-person models of cultural orientation domains as related to positive marital quality. Results provide partial evidence showing that dyadic cultural differences are associated with lower positive marital quality while cultural similarity is associated with higher positive marital quality; however, the relations are complex and suggest that the associations between wife cultural orientation and positive marital quality may depend on husband cultural orientation (and vice versa). Findings also implicate the importance of assessing spouse bidimensional cultural orientation by showing that the relation between spouse acculturation level and relationship quality may depend on his or her enculturation level. Additional nuances in the findings illustrate the importance of assessing multiple domains of cultural orientation, including language use and cultural values. We highlight several future directions for research investigating nuances in spouse cultural dynamics and relationship processes.